Advances in physical diagnosis and treatment of male erectile dysfunction - Pang, Kun; Pan, Deng; Xu, Hao; Ma, Yuyang; Wang, Jingkai; Xu, Peng; Wang, Hailuo; Zang, Guanghui (Frontiers in Physiology, 2023)
Erectile dysfunction (ED) is the most common male sexual dysfunction by far and the prevalence is increasing year after year. As technology advances, a wide range of physical diagnosis tools and therapeutic approaches have been developed for ED. At present, typical diagnostic devices include erection basic parameter measuring instrument, erection hardness quantitative analysis system, hemodynamic testing equipment, nocturnal erection measuring instrument, nerve conduction testing equipment, etc. At present, the most commonly used treatment for ED is pharmacological therapy represented by phosphodiesterase 5 inhibitors (PDE5i). As a first-line drug in clinical, PDE5i has outstanding clinical effects, but there are still some problems that deserve the attention of researchers, such as cost issues and some side effects, like visual disturbances, indigestion, myalgia, and back pain, as well as some non-response rates. Some patients have to consider alternative treatments. Moreover, the efficacy in some angiogenic EDs (diabetes and cardiovascular disease) has not met expectations, so there is still a need to continuously develop new methods that can improve hemodynamics. While drug have now been shown to be effective in treating ED, they only control symptoms and do not restore function in most cases. The increasing prevalence of ED also makes us more motivated to find safer, more effective, and simpler treatments. The exploration of relevant mechanisms can also serve as a springboard for the development of more clinically meaningful physiotherapy approaches. Therefore, people are currently devoted to studying the effects of physical therapy and physical therapy combined with drug therapy on ED. We reviewed the diagnosis of ED and related physical therapy methods, and explored the pathogenesis of ED. In our opinion, these treatment methods could help many ED patients recover fully or partially from ED within the next few decades.